Studying Features of Academic Motivation in Modern School-Children - E S Babayeva (Peoples' Friendship University of Russia (RUDN University), 2011)
The features of academic motivation in school-children and its correlation with achievement motivation in modern conditions are considered in the article. The manifestation of achievement motivation in school-children depend4ing on the grade level and sex is studied in detail.